A critical look at Global Value Chains: globalisation and competition in contemporary capitalism. The case of the automotive industry - Starosta, Guido; Fitzsimons, Alejandro (Papeles de Europa, 2023)
This article shows that the Marxian ‘law of value’ can provide solid foundations for the comprehension of the constitution and dynamics of Global Value Chains (GVC). A firm connection is thus established between the particular dynamics internal to each industry and the general dynamics of the ‘system as a whole’, which is where the greatest weakness of the GVC approach lies. Those insights are then shown through a more empirical discussion of recent transformations in the composition and governance structure of GVC resulting from the growing de-linking between innovation and manufacturing and the rise of highly concentrated global suppliers. These phenomena are illustrated through the case study of the automobile industry.